2016
DOI: 10.1039/c5nr07263h
|View full text |Cite
|
Sign up to set email alerts
|

Rational design of DNA-actuated enzyme nanoreactors guided by single molecule analysis

Abstract: The control of enzymatic reactions using nanoscale DNA devices offers a powerful application of DNA nanotechnology uniquely derived from actuation. However, previous characterization of enzymatic reaction rates using bulk biochemical assays reported suboptimal function of DNA devices such as tweezers. To gain mechanistic insight into this deficiency and to identify design rules to improve their function, here we exploit the synergy of single molecule imaging and computational modeling to characterize the three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 58 publications
1
24
0
Order By: Relevance
“…All simulations were performed using the program NAMD2 ( 76 ) with the CHARMM27 force field ( 77 , 78 ) and Allnér Mg 2 + ( 79 ) parameters. This procedure as follows has been successfully utilized in several previous studies of DNA origami nanostructures ( 80 , 81 ). An integration time step of 2 fs and periodic boundary conditions were applied in an orthogonal simulation cell.…”
Section: Methodsmentioning
confidence: 99%
“…All simulations were performed using the program NAMD2 ( 76 ) with the CHARMM27 force field ( 77 , 78 ) and Allnér Mg 2 + ( 79 ) parameters. This procedure as follows has been successfully utilized in several previous studies of DNA origami nanostructures ( 80 , 81 ). An integration time step of 2 fs and periodic boundary conditions were applied in an orthogonal simulation cell.…”
Section: Methodsmentioning
confidence: 99%
“…Incomplete closure of the arms and undesired dimer formation accounted for the observed heterogeneity. For improved proximity between the arms of a tweezer in a closed state, Dhakal et al (2016 ) leveraged TIRFM-based smFRET to systematically study the design strategy. The FRET pair attached at the two arms of the tweezers reported its conformational state.…”
Section: Characterization Of Dna Nanostructures Using Smfretmentioning
confidence: 99%
“…Our actual setup corresponds to Figure 9b, where i 1 is ~35° and the calculated value of i 2 is 68°, which is greater than the critical angle (59.1°) allowing TIR at the quartz-water interface. The depths of penetration (d) calculated using the equation [11,43,44] below are 78 and 94 nm for the green (λ = 532 nm) and red (λ = 639 nm) lasers, respectively.normald=λ4sans-serifπ(sans-serifη12sin2normali2sans-serifη22)1/2where λ is the wavelength of the incident light in vacuum. The depth of penetration relies on i 2 (ultimately i 1 ), wavelength of the incident light, and refractive indices of the mediums, however it has been demonstrated that it is independent of the polarization of the incident light [11].…”
Section: Technical Notesmentioning
confidence: 99%
“…Refracted light at an angle of incident (i 2 ) larger than the critical angle (c) undergoing total internal reflection, leading to the formation of evanescent wave. The creation of the evanescent wave allows selective excitation of fluorophores that are on or close (typically ~100 nm from the surface) [11,43,44] to the surface.…”
Section: Figurementioning
confidence: 99%